Pengungkapan pada Hubungan Sustainability Report dan Intellectual Capital terhadap Nilai Perusahaan - Shafira Gusti Permata Sari; Dwi Suhartini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research related to company value aims to analyze the relationship between sustainability reports and intellectual capital in manufacturing companies in the industrial and consumption sectors listed on the Indonesia Stock Exchange (BEI) during the 2020-2022 period. The sampling technique was purposive sampling, the results of which were 27 companies that met the research criteria. Data analysis uses SPSS Statistics 26 with descriptive statistical tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression analysis, simultaneous tests, partial tests, and coefficient of determination tests. The research results show that sustainability reports do not provide an optimal contribution to company value. However, intellectual capital, especially the employee capital aspect, is a consideration for optimizing its contribution to company value.